Pengaruh Program Matrikulasi Bahasa Arab Terhadap Peningkatan Kemampuan dan Minat Bahasa Arab Kelas X MAN 1 Pasuruan - Nabila, Syafira Azza; Ma’sum, Ali (Prosiding Konferensi Nasional Bahasa Arab, 2023)
Matriculation is an activity carried out to guide basic material which aims to equalize the abilities of new students with different backgrounds, be it education, learning methods, and also curriculum. Arabic Matriculation at MAN 1 Pasuruan is a means for students to develop their interests and abilities in Arabic which is facilitated by the school which aims to overcome students' difficulties in Arabic, students' bad perception of Arabic, and efforts to find competitors in the field of Arabic. to be developed and guided by the school. This study aims to determine the effect of the 2022 Arabic matriculation program on Arabic language skills and interests. The approach used by researchers is a qualitative approach with research instruments in the form of questionnaires, field observations, and interviews. This study shows that this program has an effect of 93% on improving students' Arabic language skills and interests.